2020
DOI: 10.1016/j.bcp.2020.114096
|View full text |Cite
|
Sign up to set email alerts
|

Animal toxins — Nature’s evolutionary-refined toolkit for basic research and drug discovery

Abstract: Venomous animals have evolved toxins that interfere with specific components of their victim's core physiological systems, thereby causing biological dysfunction that aids in prey capture, defense against predators, or other roles such as intraspecific competition. Many animal lineages evolved venom systems independently, highlighting the success of this strategy. Over the course of evolution, toxins with exceptional specificity and high potency for their intended molecular targets have prevailed, making venom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
103
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 257 publications
(312 reference statements)
0
103
0
6
Order By: Relevance
“…Antimicrobial peptides with membrane-disrupting and cytolytic activities, including those from animal venoms, have previously been shown to be antiparasitic [ 15 ]. However, very few studies have reported venom peptides with activity against nematode parasites [ 29 , 30 ], and none from ants. H. contortus is a highly virulent gastrointestinal ruminant that shows widespread drug-resistance [ 31 ], and recent reports of its multidrug resistance [ 32 ] have highlighted the need for new treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial peptides with membrane-disrupting and cytolytic activities, including those from animal venoms, have previously been shown to be antiparasitic [ 15 ]. However, very few studies have reported venom peptides with activity against nematode parasites [ 29 , 30 ], and none from ants. H. contortus is a highly virulent gastrointestinal ruminant that shows widespread drug-resistance [ 31 ], and recent reports of its multidrug resistance [ 32 ] have highlighted the need for new treatments.…”
Section: Discussionmentioning
confidence: 99%
“…We recommend that there is better communication and expectation management around natural product discovery and the drug development process, particularly regarding regulatory requirements, to manage the observed lack of follow-up. Nonetheless, the identification of numerous anthelmintic compounds from a variety of plants and even more unusual natural resources, such as funnel-web spider venoms ( Nixon et al, 2019 ; Herzig et al, 2020 ) and marine organisms ( Mayer et al, 2009 ), may because for optimism that the next ivermectin is out there.…”
Section: Inspired By Nature: Natural Products As a Source For New Antmentioning
confidence: 99%
“…This evolutionary streamlining often results in high selectivity and target-specific bioactivity, meaning that animal venoms are now considered valuable bioresources in the field of drug discovery [7]. Several blockbuster drugs have been derived from venom components [7], but they were also investigated as research tools, cosmetics, industrial enzymes or bioinsecticides [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%